Co-construction of territorial and sociodemographic data in a poor informal neighborhood with high socio-environmental vulnerability in the city of La Plata, Argentina - Canevari, Tomás (2021)
This paper presents the results of a census carried out in the largest of the 164 informal settlements currently in existence in the city of La Plata, capital of the province of Buenos Aires, Argentina. The objective is to define territorial and sociodemographic data of this poor informal neighbourhood with high socio-environmental vulnerability, paying special interest to the macro variables related to housing, education and work, as well as perceptions about the neighbourhood and future prospects. Therefore, the aim is to generate co-con-structed scientific knowledge in tandem with the community, which in turn recovers knowledge and demands from the territory with a concrete potential for transformation. This work is part of a Participatory Scientific Agenda based on the interaction of the community, political, economic and scientific-technical actors.